University integration And its relationship to time Management At university students (Journal of the College of Basic Education, 2019)
The current research aimed at a number of objectives، including measuring the measurement of university integration among university students and finding out the significance of the differences in university integration according to the sex variable، as well as the nature of the interrelations between the variables The researcher has built two measures (the university integration scale) and (the time management measure). The validity of the two measurements was taken in a manner of honesty، veracity، stability indicators in the method of testing and retesting and the method of internal consistency using the Vaccronbach equation، The sample of the building for those of the measurements was (400) students The researcher adopted the theory of (Astin) in the variable university integration and the theory ((time produced by Berg)) in the variable time organization and used the appropriate statistical methods and using the statistical bag for the psychological sciences and social ((SPSS)) to reach the results of the search has shown the results of the research To the following 1. University students enjoy university integration.2. There were no statistically significant differences in university integration according to gender variable.3. University students have the ability to organize time.4. There are no statistically significant differences in time management between the sexes.The research has put forward a number of recommendations، proposals and conclusions.